An Investigation of Chitosan-Grafted-Poly(vinyl alcohol) as an Electrolyte Membrane - Panu Danwanichakul; Pongchayont Sirikhajornnam (Journal of Chemistry, 2013)
The membrane of chitosan-grafted-poly(vinyl alcohol)/poly(vinyl alcohol) (CS-g-PVA/PVA) was investigated along with chitosan (CS), PVA, CS/PVA, and Nafion 117 membranes for transport properties of water and methanol, mechanical properties, and ionic conductivity. The ionic conductivity, σ, of the crosslinked CS-g-PVA/PVA membrane was about 4.37 mS cm−1 and the methanol permeability, PS, was 1.8×10−7 cm2s−1. These gave the selectivity, σ/PS, of 23.95 mS·s·cm−3 compared with 16.35 mS·s·cm−3 of Nafion 117 membrane. The conductivity of the crosslinked CS-g-PVA/PVA membrane was greater than others including Nafion 117 when the membranes were saturated with methanol solution of which concentration was greater than 20%. This fact and that the mechanical properties of the wet crosslinked CS-g-PVA/PVA membrane were comparable to those of other membranes made it a promising material to be used as an electrolyte membrane in a direct methanol fuel cell.